Battery and laminated structure for battery

By forming self-supporting first and second active material layers on the solid electrolyte sheet, the problem of the bipolar battery having to insert an insulating member to prevent short circuits during the manufacturing process is solved, and the effect of simple structure and short circuit suppression is achieved.

CN119678287APending Publication Date: 2025-03-21MITSUI MINING & SMELTING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380058728.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-29
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the manufacturing process, existing bipolar batteries require insulating members to prevent short circuits, resulting in increased working hours, structural complexity and weight increase.

Method used

A solid electrolyte sheet with self-supporting properties is used as the solid electrolyte layer, and the first and second active material layers are formed at any position thereof, thereby suppressing the occurrence of short circuits.

Benefits of technology

A battery design with simple structure and effective short circuit suppression is realized, simplifying the manufacturing process and reducing weight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119678287A_ABST
    Figure CN119678287A_ABST
Patent Text Reader

Abstract

Provided is a battery (10) including a self-supporting laminated structure. The battery (10) includes a solid electrolyte sheet (11) including a solid electrolyte, a first active material layer (12) formed on one main surface of the solid electrolyte sheet (11) and including a first active material, and a second active material layer (13) formed on the other main surface of the solid electrolyte sheet (11) and including a second active material. The solid electrolyte sheet (11) preferably has a first active material layer-side protruding section (11C) that protrudes outward from the peripheral edge of the first active material layer (12), or has a second active material layer-side protruding section (11D) that protrudes outward from the peripheral edge of the second active material layer (13).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a battery and a stacked structure for the battery. Background Art

[0002] In recent years, secondary batteries have received attention as a measure to prevent global warming by reducing CO2. As a type of secondary battery, it is known that there are small and high-energy-density batteries, namely bipolar batteries, which are used in power sources for vehicles, etc. The battery is formed with a positive electrode active material layer including a collector on one main surface of the solid electrolyte layer, and a negative electrode active material layer including a collector is formed on the other surface of the solid electrolyte layer. In this battery, in order to prevent the positive electrode active material layer and the negative electrode active material layer from being offset relative to the main surface of the solid electrolyte, the area of ​​the positive electrode active material layer and the negative electrode active material layer, namely the collector, is increased relative to the area of ​​the main surface of the solid electrolyte layer. However, the collectors are sometimes electrically connected to each other and short-circuited, and therefore, insulating members are usually inserted between the collectors.

[0003] However, in the bipolar battery described above, since the insulating member needs to be inserted, the manufacturing man-hours increase accordingly, and the structure of the battery becomes complicated. In addition, the weight increases accordingly with the insertion of the insulating member.

[0004] In view of the above problems, Patent Document 1 discloses a technique of using a current collector having higher conductivity in the thickness direction than in the surface direction so that current flows approximately only in the thickness direction.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2007-213930 Summary of the invention

[0008] However, the technology described in Patent Document 1 requires that the current collector be composed of a non-conductive polymer material and conductive conductive particles, which limits the selection of materials and complicates the production process of the current collector.

[0009] Therefore, an object of the present invention is to provide a battery having a simple structure and capable of suppressing the occurrence of a short circuit.

[0010] The present inventors have conducted intensive studies to solve the above problems and have found that by using a solid electrolyte sheet as a solid electrolyte layer, an electrode layer can be formed at any position of the solid electrolyte layer, thereby suppressing the occurrence of short circuits.

[0011] That is, the present invention provides a battery including a self-supporting stacked structure, comprising:

[0012] a solid electrolyte sheet comprising a solid electrolyte;

[0013] a first active material layer formed on one main surface of the solid electrolyte sheet and containing a first active material; and

[0014] The second active material layer is formed on the other main surface of the solid electrolyte sheet and contains a second active material.

[0015] In addition, the present invention provides a self-supporting battery stack structure comprising:

[0016] a solid electrolyte sheet comprising a solid electrolyte;

[0017] a first active material layer formed on one main surface of the solid electrolyte sheet and containing a first active material; and

[0018] The second active material layer is formed on the other main surface of the solid electrolyte sheet and contains a second active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 (a) is a perspective view of a battery stack structure according to an embodiment of the present invention, Figure 1 (b) is Figure 1 (a) Cross-sectional view along line II.

[0020] Figure 2 is a perspective view of a battery stack structure according to another embodiment of the present invention. Figure 2 (b) is Figure 2 (a) Cross-sectional view along line II-II.

[0021] Figure 3 (a) is a diagram showing the method for manufacturing Figure 2 A perspective view of an assembly of a battery stack structure shown in (a), Figure 3 (b) is Figure 3 (a) is a cross-sectional view taken along line III-III. DETAILED DESCRIPTION

[0022] Hereinafter, the present invention will be described based on preferred embodiments thereof.

[0023] Figure 1 It is a schematic structural diagram of a battery according to an embodiment of the present invention. Figure 1 (a) is a three-dimensional diagram of a stacked structure of a battery. Figure 1 (b) is Figure 1 (a) is a cross-sectional view when cut along the dotted line II.

[0024] Figure 1The battery 10 shown has a self-supporting solid electrolyte sheet 11 containing a solid electrolyte, a first active material layer 12 formed on a main surface 11A of the solid electrolyte sheet 11, and a second active material layer 13 formed on a back surface 11B of the solid electrolyte sheet 11. The battery 10 includes a battery stack structure having three components 11, 12, and 13. In the stack structure, the three components 11, 12, and 13 are integrated, so as described later, the stack structure itself has self-supporting properties and is easy to handle.

[0025] In this specification, the term "integrated" means that two adjacent members among the three members 11, 12, and 13 are arranged so as not to be separable in a conventional process.

[0026] In this specification, the term "self-supporting property" refers to the rigidity of a stacked structure, and "self-supporting property" means that the stacked structure can maintain its shape without using a supporting member other than the stacked structure.

[0027] Moreover, in this specification, a sheet refers to a component having a first main surface and a second main surface located on the opposite side thereof, and the distance between the two main surfaces, i.e., the thickness, is extremely small relative to the longitudinal and lateral dimensions of the main surfaces (for example, the thickness is less than 1 / 100 relative to the longitudinal and lateral dimensions).

[0028] The battery 10 of this embodiment uses a self-supporting solid electrolyte sheet 11. Therefore, it is possible to provide a battery 10 including a self-supporting laminated structure, and as described below, the first active material layer 12 and the second active material layer 13 can be formed at any position on the solid electrolyte sheet 11. Figure 1 As shown, for example, the first active material layer 12 and the second active material layer 13 can be arranged substantially in the center of the main surface 11A and the back surface 11B of the solid electrolyte sheet 11. As a result, the solid electrolyte sheet 11 has a first active material layer side extension portion (hereinafter sometimes referred to as "first outer peripheral edge portion") 11C extending outward from the periphery of the first active material layer 12, or has a second active material layer side extension portion (hereinafter sometimes referred to as "second outer peripheral edge portion") 11D extending outward from the periphery of the second active material layer 13.

[0029] Therefore, when the battery 10 of the present embodiment is assembled into a bipolar battery, it is possible to effectively suppress the adjacent first active material layer 12 and second active material layer 13 from contacting and short-circuiting. That is, by using the self-supporting solid electrolyte sheet 11 as the solid electrolyte layer, it is possible to provide a battery 10 including a self-supporting stacked structure, which can suppress the occurrence of short circuits between the electrodes constituting the battery 10, that is, the first active material layer 12 and the second active material layer 13, with a simple structure.

[0030] Specifically, when the area of ​​the main surface 11A and the back surface 11B of the solid electrolyte sheet 11 is A, the area of ​​the main surface 12A or 13A of the first active material layer 12 or the second active material layer 13 is B, and the area of ​​the larger one of the first peripheral edge portion 11C and the second peripheral edge portion 11D of the solid electrolyte sheet 11 is C, the ratio of the area C to the area A can be preferably 1 / 20 or less, more preferably 1 / 25 or less, and further preferably 1 / 30 or less. That is, there is no need to excessively increase the area of ​​the solid electrolyte sheet 11 in order to suppress the occurrence of a short circuit, so the structure of the battery 10 can be simplified, and the battery 10 can be miniaturized.

[0031] The first outer peripheral edge portion 11C and the second outer peripheral edge portion 11D are regions located outside the regions where the first active material layer 12 and the second active material layer 13 are disposed in the solid electrolyte sheet 11 .

[0032] It should be noted that the first outer peripheral portion 11C preferably extends from the entire peripheral region of the first active material layer 12 . Similarly, the second outer peripheral portion 11D preferably extends from the entire peripheral region of the second active material layer 13 .

[0033] Figure 2 This is a schematic structural diagram of a battery stack structure according to another embodiment of the present invention. Figure 2 (a) is a three-dimensional diagram of a stacked structure. Figure 2 (b) is Figure 2 (a) is a cross-sectional view when cut along the dotted line II-II. Figure 2 In, with Figure 1 In the laminated structure shown, the same or similar components are denoted by the same reference numerals.

[0034] Figure 2 The stacked structure of the battery 20 shown is in the same manner as the above Figure 1 In the related embodiment, the ratio of the area C to the area A is set to 0. That is, the area A of the solid electrolyte sheet 11 is made the same as the area B of the first active material layer 12 and the second active material layer 13, and the first outer peripheral edge portion 11C and the second outer peripheral edge portion 11D of the solid electrolyte sheet 11 are not present. Therefore, in a plan view of the stacked structure, the periphery of the solid electrolyte sheet 11, the periphery of the first active material layer 12, and the periphery of the second active material layer 13 are located at the same position.

[0035] In the present embodiment, since the area A of the solid electrolyte sheet 11 is made equal to the area B of the first active material layer 12 and the second active material layer 13, it is obvious that the structure of the battery 20 can be simplified and further miniaturization of the battery 20 can be achieved. Therefore, even when a plurality of batteries 20 are connected to form a predetermined battery unit, the battery unit can be miniaturized.

[0036] It should be noted that although the known documents illustrate Figure 2 The battery structure of the form shown is simply recorded for the sake of convenience. As shown in the battery 20 of this embodiment, the area A of the solid electrolyte sheet 11 is substantially different from the area B of the first active material layer 12 and the second active material layer 13.

[0037] In fact, Figure 3 (a) and Figure 3 As shown in (b), Figure 2 The laminated structure used in the battery 20 shown is obtained by setting a punching-out portion 25 in the assembly 20X and punching the assembly 20X in the thickness direction at the punching-out portion 25. This manufacturing method is a method that is not known in the past, and the battery 20 has a structure that is manufactured by this unknown method. Figure 2 The stacked structure shown is naturally also previously unknown. Figure 3 (a) is a diagram showing the method for manufacturing Figure 2 (a) is a perspective view of a battery assembly, Figure 3 (b) is Figure 3 (a) is a cross-sectional view taken along line III-III.

[0038] It should be noted that the aforementioned punching-out portion 25 refers to a region that penetrates all of the solid electrolyte sheet 11 , the first active material layer 12 , and the second active material layer 13 in the thickness direction in a plan view of the stacked structure.

[0039] The thickness of the solid electrolyte sheet 11 is preferably, for example, 3 μm or more, preferably 5 μm or more, and particularly preferably 10 μm or more. On the other hand, the thickness of the solid electrolyte sheet 11 is preferably, for example, 100 μm or less, preferably 80 μm or less, and particularly preferably 15 μm or less. When the thickness of the solid electrolyte sheet 11 is within the above range, the relative density of the solid electrolyte sheet 11 and thus the solid electrolyte is increased, and the ion conductivity can be increased while the electronic conductivity is kept low, and the mechanical strength can also be improved.

[0040] The thickness of the solid electrolyte sheet 11 can be measured, for example, by microscopic observation of a cross section of the solid electrolyte sheet 11. Alternatively, the thickness can be measured using a thickness gauge. In either case, the thickness is measured at any 10 or more locations, and the arithmetic mean thereof is defined as the thickness of the solid electrolyte sheet 11.

[0041] The solid electrolyte sheet 11 used in the present invention preferably has a solid electrolyte and a support (not shown). As a result, the solid electrolyte sheet 11 has a higher self-supporting property and the handling property is further improved. In addition, the stacked structure constituting the above-mentioned battery 10, 20 can be obtained well.

[0042] The proportion of the solid electrolyte contained in the solid electrolyte sheet is, for example, preferably 50.0% by mass or more, preferably 70.0% by mass or more, and particularly preferably 90.0% by mass or more. On the other hand, the proportion of the solid electrolyte contained in the solid electrolyte sheet is, for example, preferably 99.5% by mass or less. When the proportion of the solid electrolyte in the solid electrolyte sheet 11 is within the above range, a solid electrolyte sheet 11 having a better relative density, ion conductivity and mechanical strength can be produced. It should be noted that the upper limit of the proportion of the solid electrolyte contained in the solid electrolyte sheet is 100% by mass.

[0043] In addition, the porosity of the solid electrolyte sheet 11 may be, for example, 1% or more, 1.5% or more, or 2% or more. On the other hand, the porosity of the solid electrolyte sheet 11 is, for example, preferably 50% or less, more preferably 45% or less, and further preferably 30% or less. When the porosity of the solid electrolyte sheet 11 is within the above range, the solid electrolyte sheet 11 having a better relative density, ion conductivity, and mechanical strength can be obtained.

[0044] The support is preferably a porous substrate. The solid electrolyte is preferably supported in pores of the porous substrate.

[0045] The "porous" of the porous substrate means a state of having a plurality of fine pores.

[0046] The porous substrate preferably has fine pores extending from one surface to the other surface of the porous substrate.

[0047] The size of the pores may be any size as long as the pores are filled with at least a part of the solid electrolyte particles when the solid electrolyte sheet 11 is formed.

[0048] The pores may be connected to each other.

[0049] The porous substrate is preferably a fiber sheet in particular from the viewpoint of providing sufficient self-supporting properties and appropriate flexibility to the solid electrolyte sheet 11. Examples of the fiber sheet include nonwoven fabrics, woven fabrics, and knitted fabrics, and nonwoven fabrics are particularly preferred.

[0050] When the porous base sheet is a fiber sheet, "porous" means a state in which there are pores generated between fibers.

[0051] For nonwoven fabrics, there are various types according to the type of fiber used to make the nonwoven fabric (fiber length, fiber diameter, fiber material, etc.), the type of manufacturing method (such as web forming method, web fiber entanglement method, etc.), etc. The nonwoven fabric used as a porous substrate sheet is not particularly limited as long as the desired solid electrolyte sheet can be obtained. As nonwoven fabrics, for example, fiber orthogonal nonwoven fabrics, long fiber nonwoven fabrics, short fiber nonwoven fabrics, wet nonwoven fabrics, dry nonwoven fabrics, air-laid nonwoven fabrics, card-type nonwoven fabrics, parallel nonwoven fabrics, cross-type nonwoven fabrics, random nonwoven fabrics, spunbond nonwoven fabrics, meltblown nonwoven fabrics, flash spun nonwoven fabrics, chemically bonded nonwoven fabrics, spunlace nonwoven fabrics, needle-punched nonwoven fabrics, stitched nonwoven fabrics, thermally bonded nonwoven fabrics, foamed fiber (burst fiber) nonwoven fabrics, open beam nonwoven fabrics, split film nonwoven fabrics, composite nonwoven fabrics, laminated nonwoven fabrics, coated nonwoven fabrics, laminated nonwoven fabrics, etc. Among these, a cross nonwoven fabric is preferred. From the perspective of easily adjusting the strength ratio in the length direction X and the width direction Y, the weight per unit area, etc., a cross nonwoven fabric is preferred. The strength ratio in the length direction X and the width direction Y of the cross nonwoven fabric is preferably uniformly adjusted. The weight per unit area of ​​the cross nonwoven fabric can be a low weight per unit area or a high weight per unit area. As a cross nonwoven fabric, for example, a polyolefin mesh fabric (refer to Japanese Patent Publication No. 2007-259734) can be cited. It should be noted that, regarding the specific weight per unit area of ​​the nonwoven fabric, for example, it can be the same as that described in Japanese Patent Publication No. 2018-129307, so the description is omitted here.

[0052] The material, porosity, air permeability, thickness, etc. constituting the porous substrate may be the same as those used in a general solid electrolyte sheet. For example, it may be the same as the porous substrate sheet described in Japanese Patent Publication No. 2018-129307, so the description is omitted here.

[0053] The solid electrolyte layer is a layer that conducts lithium ions between the positive electrode layer and the negative electrode layer in a solid battery. In order to achieve this purpose, the solid electrolyte contained in the solid electrolyte layer preferably contains a crystalline phase having a argyrodite-type crystal structure. The argyrodite-type crystal structure refers to a crystal structure possessed by a group of compounds derived from a mineral represented by the chemical formula: Ag8GeS6. Whether the solid electrolyte has a crystalline phase of the argyrodite-type crystal structure can be confirmed by, for example, measurement using X-ray diffraction (hereinafter also referred to as "XRD"). For example, in a diffraction pattern measured based on XRD using CuKα1 rays, the crystalline phase of the argyrodite-type crystal structure shows characteristic diffraction peaks at 2θ=25.5°±1.0°, 30.0°±1.0°, and 30.9°±1.0°. In addition, depending on the type of element constituting the solid electrolyte, in addition to the above-mentioned diffraction peaks, characteristic diffraction peaks may be shown at 2θ=15.3°±1.0°, 18.0°±1.0°, 44.3°±1.0°, 47.2°±1.0°, 51.7°±1.0°, 58.3°±1.0°, 60.7°±1.0°, 61.5°±1.0°, 70.4°±1.0°, and 72.6°±1.0°. For example, the data of PDF No. 00-034-0688 are used to identify the diffraction peaks derived from the argyrodite type crystal structure.

[0054] The solid electrolyte preferably contains at least lithium (Li), phosphorus (P) and sulfur (S); more preferably contains at least lithium (Li), phosphorus (P), sulfur (S) and halogen (X). In this case, from the viewpoint of improving lithium ion conductivity, the solid electrolyte preferably has a composition formula (I): Li a PS b X c (X is at least one of fluorine (F) element, chlorine (Cl) element, bromine (Br) element, and iodine (I) element).

[0055] In the composition formula (I), a, which represents the molar ratio of the Li element, is preferably 3.0 or more, preferably 4.0 or more, and particularly preferably 5.0 or more. On the other hand, a is preferably 6.5 or less, preferably 5.9 or less, and particularly preferably 5.6 or less. When a is within this range, the cubic argyrodite-type crystal structure near room temperature (25° C.) is more stable, so that lithium ion holes can be fully introduced into the structure, and as a result, the lithium ion conductivity can be effectively improved.

[0056] In the composition formula (I), b is preferably 3.5 or more, preferably 4.0 or more, and particularly preferably 4.2 or more. On the other hand, b is preferably 5.5 or less, preferably 4.9 or less, and particularly preferably 4.7 or less. When b is within the above range, the argyrodite-type crystal structure near room temperature (25° C.) is more stable, and lithium ion conductivity is effectively improved.

[0057] In composition formula (I), c is, for example, preferably 0.1 or more, particularly preferably 1.1 or more, and particularly preferably 1.4 or more. On the other hand, c is, for example, preferably 2.5 or less, particularly preferably 2.0 or less, and particularly preferably 1.8 or less.

[0058] In addition, the solid electrolyte can also be used with the composition formula (II): Li 7-d PS 6-d X d The composition represented by the composition formula (II) is the stoichiometric composition of the argyrodite type crystal phase. In the composition formula (II), X has the same meaning as that of the composition formula (I).

[0059] In composition formula (II), d is, for example, preferably 0.4 or more, more preferably 0.8 or more, and particularly preferably 1.2 or more. On the other hand, d is, for example, preferably 2.2 or less, more preferably 2.0 or less, and particularly preferably 1.8 or less.

[0060] In addition, the solid electrolyte can also be used with a composition formula (III): Li 7-d-2e PS 6-d-e X d The argyrodite-type crystal phase having the composition represented by the composition formula (III) is generated, for example, by the reaction of the argyrodite-type crystal phase having the composition represented by the composition formula (II) with P2S5 (phosphorus pentasulfide).

[0061] In the composition formula (III), e is a value indicating that the Li2S component deviates from the stoichiometric composition shown in the composition formula (II). For example, e is preferably greater than -0.9, preferably greater than -0.6, and particularly preferably greater than -0.3. On the other hand, the aforementioned e is preferably less than (-d+2.0), preferably less than (-d+1.6), and particularly preferably less than (-d+1.0).

[0062] In the solid electrolyte, the atomic ratio X / P of the X element relative to the P element is, for example, preferably greater than 1.0, more preferably greater than 1.1, more preferably greater than 1.2, and more preferably greater than 1.4. On the other hand, the atomic ratio X / P is, for example, preferably less than 2.5, more preferably less than 2.3, and more preferably less than 2.2. When the atomic ratio X / P is within the above range, the lithium ion conductivity is further improved. The atomic ratio X / P can be measured by, for example, high-frequency inductively coupled plasma emission spectrometry (ICP emission spectrometry) or SEM-EDS analysis.

[0063] In particular, when the X element contains at least the Cl element and the Br element, the atomic ratio (Cl+Br) / P of the total of the Cl element and the Br element relative to the P element is, for example, preferably greater than 1.0, more preferably greater than 1.1, more preferably greater than 1.2, and more preferably greater than 1.4. On the other hand, the atomic ratio (Cl+Br) / P is, for example, preferably less than 2.5, more preferably less than 2.3, and more preferably less than 2.0. When the atomic ratio (Cl+Br) / P is within the above range, the lithium ion conductivity is further improved, so it is preferred. The atomic ratio (Cl+Br) / P can be measured, for example, by elemental analysis using high-frequency inductively coupled plasma emission spectrometry (ICP emission spectrometry) or a scanning electron microscope equipped with EDS (SEM-EDS).

[0064] Among the above composition formulas (I) to (III), the solid electrolyte is particularly preferably composed of formula (IV): Li 7-d PS 6- d Cl d1 Br d2 Substance shown.

[0065] In the above composition formula (IV), the total molar ratio d (= d1 + d2) of Cl and Br is preferably greater than 1.0, preferably greater than 1.2, and particularly preferably greater than 1.4. On the other hand, the above total molar ratio d is preferably less than 2.5, preferably less than 2.0, particularly preferably less than 1.8, and further preferably less than 1.7. When the above total molar ratio d is within the above range, the generation of heterogeneous phases can be fully controlled, and the reduction of ion conductivity can be effectively suppressed.

[0066] In the above composition formula, the ratio of the molar ratio of Br to the molar ratio of Cl (d2 / d1) is, for example, preferably 0.1, preferably 0.3 or more, and particularly preferably 0.5 or more. On the other hand, the ratio of the above molar ratio is, for example, preferably 10 or less, preferably 5 or less, and particularly preferably 3 or less. When the ratio of the above molar ratio is within the above range, the lithium ion conductivity can be further improved.

[0067] In the above composition formula, d1 representing the molar ratio of Cl is preferably 0.3 or more, preferably 0.4 or more, and particularly preferably 0.6 or more. On the other hand, d1 is preferably 1.5 or less, preferably 1.2 or less, and particularly preferably 1.0 or less. When d1 is above the above lower limit, the lithium ion conductivity can be further improved. On the other hand, when d1 is below the above upper limit, the above solid electrolyte is easily obtained.

[0068] In the above composition formula, d2, which represents the molar ratio of Br, is preferably 0.3 or more, preferably 0.4 or more, and particularly preferably 0.6 or more. On the other hand, d2 is preferably 1.5 or less, preferably 1.2 or less, and particularly preferably 1.0 or less. When d2 is above the above lower limit, a solid electrolyte is easily obtained. On the other hand, when d2 is below the above upper limit, lithium ion conductivity can be further improved.

[0069] When the solid electrolyte is any one of the composition formulas (I), (II), (III) and (IV), it is preferred that the X element contains a Br element because the lithium ion conductivity is further improved.

[0070] The first active material layer 12 and the second active material layer 13 may be respectively composed of a positive electrode active material or a negative electrode active material. When the first active material contained in the first active material layer 12 is a positive electrode active material and the second active material contained in the second active material layer 13 is a negative electrode active material, the battery 10 may be used as a bipolar battery, for example. Specifically, by connecting two stacked structures in series so that the first active material layer 12 in one stacked structure and the second active material layer 13 in the other stacked structure are opposite to each other via a current collector, a bipolar battery can be provided.

[0071] The first active material contained in the first active material layer 12 and the second active material contained in the second active material layer 13 may be either a positive electrode active material or a negative electrode active material.

[0072] Examples of positive electrode active materials include oxide active materials containing lithium and transition metals. Specifically, examples include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and other rock salt layered active materials; lithium manganate (LiMn2O4), Li(Ni 0.5 Mn 1.5 )O4、Li 1+x Mn 2-x-y M yO4 (M is one or more selected from the group consisting of Al, Mg, Co, Fe, Ni, Zn) and other spinel active materials; lithium titanate (Li x TiO y ), LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4 and other olivine-type active materials, etc.

[0073] Examples of the negative electrode active material include Si and Si alloys; carbon materials such as graphite and hard carbon; various oxides such as lithium titanate; metallic lithium, and lithium alloys.

[0074] The content of the active material contained in the first active material layer 12 and the second active material layer 13 is not particularly limited as long as it can function as an electrode. When the first active material layer 12 or the second active material layer 13 contains a positive electrode active material, when the total mass of the active material layer is set to 100 mass%, the content of the positive electrode active material is, for example, preferably 50 mass% or more, more preferably 65 mass% or more, and more preferably 75 mass% or more. On the other hand, the content of the positive electrode active material can be, for example, 99 mass% or less.

[0075] When the first active material layer 12 or the second active material layer 13 contains a negative electrode active material, when the total mass of the active material layer is set to 100 mass %, the content of the negative electrode active material is, for example, preferably 20 mass % or more, more preferably 40 mass % or more, and more preferably 70 mass % or more. On the other hand, the content of the negative electrode active material can be, for example, 99 mass % or less.

[0076] The first active material layer 12 and the second active material layer 13 may contain a solid electrolyte. The solid electrolyte is not particularly limited. The solid electrolyte is preferably the above-mentioned solid electrolyte. The content of the solid electrolyte contained in the first active material layer 12 and the second active material layer 13 is not particularly limited as long as the electrode containing the first active material layer 12 and the second active material layer 13 can perform the desired function. When the total mass of the active material layer is set to 100 mass%, the content of the solid electrolyte can be, for example, 1 mass% or more and 80 mass% or less in the first active material layer 12 and the second active material layer 13, respectively and independently.

[0077] The first active material layer 12 and the second active material layer 13 may contain a conductive material, a binder, and various additives as needed. As the conductive material, for example, carbon materials such as VGCF (vapor grown carbon fiber) and carbon nanofibers, and metal materials can be cited. As the binder, for example, materials such as polyvinylidene fluoride (PVdF), carboxymethyl cellulose (CMC), butadiene rubber (BR) and styrene butadiene rubber (SBR), or a combination thereof can be cited.

[0078] Next, Figure 1 A preferred method for manufacturing a battery of the present invention will be described by taking the method for manufacturing the battery 10 of the illustrated embodiment as an example.

[0079] First, the solid electrolyte sheet 11 is manufactured. This manufacturing is roughly divided into the following steps.

[0080] (1) Step of preparing a laminated member.

[0081] (2) A step of producing a laminated body using the laminated member.

[0082] (3) A step of pressurizing the laminate.

[0083] (4) A step of peeling and removing the carrier sheet from the laminate.

[0084] Hereinafter, each step will be described.

[0085] (1) Step of preparing a laminated member

[0086] In this step, a laminated member is prepared, the laminated member comprising: a carrier sheet and a coating film formed on the carrier sheet and containing a solid electrolyte. The carrier sheet preferably has a strength that can support the coating film and has flexibility.

[0087] The thickness of the carrier sheet can be appropriately selected according to the material constituting these carrier sheets, and it is preferred that these carrier sheets have a thickness to the extent of self-supporting. In addition, a carrier sheet with flexibility can also be made by adjusting the thickness of the carrier sheet. The thickness of the carrier sheet is not particularly limited, and for example, it can be 5 μm or more, or 10 μm or more, or 15 μm or more. On the other hand, the thickness of the carrier sheet can be, for example, 1000 μm or less, or 200 μm or less, and particularly 100 μm or less.

[0088] The material constituting the carrier sheet is preferably at least one of resin, glass and metal. That is, the carrier sheet is preferably at least one of carrier resin, carrier glass and carrier metal foil. The carrier sheet may also be a multilayer structure in which two or more of the carrier resin, carrier glass and carrier metal foil are stacked, for example.

[0089] Examples of the material contained in the carrier resin include acrylic resins, polyester resins, cellulose derivative resins, polyvinyl acetal resins, polyvinyl butyral resins, vinyl chloride-vinyl acetate copolymers, chlorinated polyolefins, and copolymers of these resins.

[0090] As the carrier glass, for example, glass cloth which is a woven fabric of glass fibers or the like can be used.

[0091] Examples of the material constituting the carrier metal foil include copper, stainless steel, aluminum, nickel, silver, gold, chromium, cobalt, tin, zinc, and alloys thereof.

[0092] There may not be other layers between the carrier sheet and the coating film, or there may be one or more than two layers of other layers between the two. In either case, the carrier sheet and the coating film are preferably stacked in a peelable manner. The carrier sheet and the coating film are stacked in a peelable manner, which means that the two can be peeled off in a manner where their respective structures are not destroyed. The peel strength of the carrier sheet and the coating film is, for example, preferably less than 10N / 10mm, wherein preferably less than 7N / 10mm, particularly preferably less than 4N / 10mm. This is because, when the peel strength is within the aforementioned range, the carrier sheet and the coating film can be well peeled off. As a method for measuring peel strength, for example, the following can be cited: the laminated body stacked with the layer as the object is cut into a strip of 10mm in width, and a method for interlayer peeling test (180 degree peeling, test speed 50mm / minute) is performed using a tensile compression testing machine.

[0093] When the carrier sheet and the coating film are laminated in a releasable manner, the surface of the carrier sheet that faces the coating film may be subjected to a peeling treatment. Examples of the peeling treatment include surface smoothing and application of a resin peeling agent.

[0094] The coating film formed on the carrier sheet comprises a solid electrolyte and a solvent. Examples of the solvent include, independently, non-polar solvents such as heptane, methylcyclohexane and toluene; aprotic polar solvents such as methyl isobutyl ketone and cyclohexanone; or a mixture thereof.

[0095] The solid electrolyte contained in the coating film has a particle form. The particle size is obtained by using a laser diffraction scattering particle size distribution measurement method to obtain a volume cumulative particle size D when the cumulative volume is 50% by volume. 50 and is preferably, for example, 0.1 μm or more, more preferably 0.3 μm or more, and even more preferably 0.5 μm or more. 50 For example, it is preferably 20 μm or less, more preferably 10 μm or less, and further preferably 5 μm or less.

[0096] Examples of a method for mixing the solid electrolyte and the solvent include an ultrasonic homogenizer, an oscillator, a thin film rotary mixer, a dissolver, a homomixer, a kneader, a roll mill, a sand mill, an attritor, a ball mill, a vibration mill, and a high-speed impeller mill.

[0097] After the solid electrolyte and the solvent are mixed in this way, the slurry obtained by the mixture is applied to one side of the carrier sheet. As the coating method, for example, there can be mentioned: a doctor blade method, a die coating method, a gravure coating method, a spray coating method, an electrostatic coating method, a rod coating method, etc. By applying the slurry on one side of the carrier sheet, a coating film is formed.

[0098] From the viewpoint of the coating property of the slurry, the solid content concentration of the coating film thus obtained is, for example, preferably 40% by mass or more, more preferably 50% by mass or more, and more preferably 60% by mass or more. On the other hand, the solid content concentration is, for example, preferably 90% by mass or less, and more preferably 80% by mass or less.

[0099] After the coating is formed, the liquid component can be appropriately removed. As a method for removing the liquid component, for example, warm air drying, hot air drying, infrared drying, reduced pressure drying, induction heating drying, etc. can be cited. Thus, a laminated component having a carrier sheet and a coating film formed on the carrier sheet and containing a solid electrolyte is prepared.

[0100] (2) Process of manufacturing a laminated body using a laminated member

[0101] The laminated structure prepared in the step (1) is arranged on the support in such a manner that the coating film containing the solid electrolyte in the laminated structure is opposite to the support formed by the above-mentioned porous substrate, thereby obtaining a laminated structure in which the laminated structure is laminated on the support. By containing an appropriate amount of solvent in the coating film, a part of the coating film is filled into the pores of the porous substrate. This filling becomes effective in the subsequent step, i.e., the pressurization step.

[0102] (3) Step of Pressurizing the Laminated Body

[0103] The process of pressurizing the stack is carried out as follows: in the case where the solid electrolyte sheet has a support formed by a porous substrate, the coating, i.e., at least a portion of the solid electrolyte particles, is effectively filled into the pores of the porous substrate. To achieve this purpose, the stack is pressurized at least in the thickness direction. For example, a uniaxial press can be used to pressurize the stack in the thickness direction. Alternatively, the stack can be isotropically pressurized as a whole by CIP (cold isostatic pressing).

[0104] It should be noted that the pressurization pressure can be appropriately adjusted according to the type of porous substrate constituting the laminate, the amount of solid electrolyte contained in the coating film, etc. As a specific pressurization pressure, for example, it is preferably 100 MPa or more, more preferably 350 MPa or more, and further preferably 700 MPa or more.

[0105] (4) Step of peeling and removing the carrier sheet from the laminate

[0106] In this step, the carrier sheet is peeled off from the laminated body after the pressurization. By peeling off the carrier sheet from the laminated body in this way, the target solid electrolyte sheet 11, that is, the solid electrolyte sheet 11 in which the support body is buried in the solid electrolyte can be obtained.

[0107] Next, the first active material layer 12 and the second active material layer 13 are formed on the main surface 11A and the back surface 11B of the solid electrolyte sheet 11 obtained as described above.

[0108] First, an electrode slurry containing an active material and a solvent is prepared. As described above, the active material is a positive electrode active material or a negative electrode active material, and typically has a particle form. The size of the active material particles is determined by the volume cumulative particle size D at a cumulative volume of 50% by laser diffraction scattering particle size distribution measurement method. 50 and is preferably, for example, 0.1 μm or more, more preferably 1 μm or more, and even more preferably 3 μm or more. 50 For example, it is preferably 100 μm or less, more preferably 30 μm or less, and even more preferably 10 μm or less.

[0109] Examples of the solvent include nonpolar solvents such as heptane, methylcyclohexane, and toluene; aprotic polar solvents such as methyl isobutyl ketone and cyclohexanone; and mixed solutions thereof.

[0110] The electrode slurry may contain other materials in addition to the active material and the solvent. Examples of other materials include a binder, a conductive material, a solid electrolyte, and various additives.

[0111] Examples of the mixing method for the electrode slurry include an ultrasonic homogenizer, an oscillator, a thin film rotary mixer, a dissolver, a homomixer, a kneader, a roll mill, a sand mill, an attritor, a ball mill, a vibration mill, and a high-speed impeller mill.

[0112] From the viewpoint of the coating property of the slurry, the solid content concentration of the electrode slurry is preferably, for example, 40% by mass or more, more preferably 50% by mass or more, and more preferably 60% by mass or more. On the other hand, the solid content concentration is preferably, for example, 90% by mass or less, and more preferably 80% by mass or less.

[0113] After the electrode slurry is prepared, it is applied to the main surface 11A and the back surface 11B of the solid electrolyte sheet 11. As a coating method, for example, it can be cited: a doctor blade method, a die coating method, a gravure coating method, a spray coating method, an electrostatic coating method, a rod coating method, etc. After the coating is formed, it is dried to remove the liquid component. By appropriately setting the drying conditions, the amount of liquid component contained in the coating can be adjusted to a desired range. As a drying method, for example, it can be cited: warm air drying, hot air drying, infrared drying, reduced pressure drying, induction heating drying, etc. Thereby, an active material layer 2 is formed in a substantially dry state. By appropriately adjusting the coating amount of the electrode slurry, a first active material layer 12 and a second active material layer 13 having a desired thickness can be formed.

[0114] In manufacturing Figure 2 When the battery 20 is shown, after the above steps, an additional Figure 3 The blanking process shown is sufficient.

[0115] The battery thus obtained can be used as a solid battery. In this specification, the solid battery includes not only a solid battery that does not contain any liquid substance or gel-like substance as an electrolyte, but also a method that contains, for example, 50% by mass or less, 30% by mass or less, or 10% by mass or less of a liquid substance or gel-like substance as an electrolyte.

[0116] In view of the above-mentioned embodiments, the present invention includes the following batteries and battery stack structures.

[0117] [1] A battery including a self-supporting laminate structure, comprising:

[0118] a solid electrolyte sheet comprising a solid electrolyte;

[0119] a first active material layer formed on one main surface of the solid electrolyte sheet and containing a first active material; and

[0120] The second active material layer is formed on the other main surface of the solid electrolyte sheet and contains a second active material.

[0121] [2] The battery according to [1], wherein the solid electrolyte sheet has a first active material layer side extension extending outward from the periphery of the first active material layer, or has a second active material layer side extension extending outward from the periphery of the second active material layer.

[0122] [3] The battery according to [1] or [2], wherein the area of ​​the first active material layer side extension and the second active material layer side extension in plan view, whichever is larger, is defined as C,

[0123] When the area of ​​the solid electrolyte sheet in a plan view is defined as A,

[0124] The ratio of area C to area A is 1 / 20 or less.

[0125] [4] The battery according to any one of [1] to [3], wherein the solid electrolyte sheet has a thickness of 3 μm to 100 μm.

[0126] [5] The battery according to any one of [1] to [4], wherein the proportion of the solid electrolyte in the solid electrolyte sheet is 50.0 mass % or more and 99.5 mass % or less.

[0127] [6] The battery according to any one of [1] to [5], wherein the solid electrolyte sheet has a support.

[0128] [7] The battery according to [6], wherein the support is formed of a porous substrate, and the solid electrolyte is supported in pores of the porous substrate.

[0129] [8] The battery according to any one of [1] to [7], wherein the solid electrolyte contains a crystal phase having an argyrodite-type crystal structure.

[0130] [9] The battery according to any one of [1] to [8], wherein the first active material is a positive electrode active material and the second active material is a negative electrode active material.

[0131]

[10] The battery according to [9], wherein two stacked structures are connected in series so that the first active material layer in one stacked structure and the second active material layer in the other stacked structure face each other via a current collector.

[0132]

[11] The battery according to any one of [1] to [8], wherein the first active material and the second active material are both positive electrode active materials or negative electrode active materials.

[0133]

[12] A self-supporting battery stack structure comprising:

[0134] a solid electrolyte sheet comprising a solid electrolyte;

[0135] a first active material layer formed on one main surface of the solid electrolyte sheet and containing a first active material; and

[0136] The second active material layer is formed on the other main surface of the solid electrolyte sheet and contains a second active material.

[0137]

[13] The battery stack structure according to

[12] , wherein the battery stack structure has a predetermined punching portion at its outer edge for penetrating the solid electrolyte sheet, the first active material layer, and the second active material layer in the thickness direction.

[0138] Industrial Applicability

[0139] According to the present invention, it is possible to provide a battery having a simple structure and capable of suppressing the occurrence of a short circuit.

Claims

1. A battery comprising a self-supporting stacked structure, comprising: a solid electrolyte sheet comprising a solid electrolyte; a first active material layer formed on one main surface of the solid electrolyte sheet and containing a first active material; and The second active material layer is formed on the other main surface of the solid electrolyte sheet and contains a second active material.

2. The battery according to claim 1, wherein The solid electrolyte sheet has a first active material layer-side extending portion extending outward from a peripheral edge of the first active material layer, or has a second active material layer-side extending portion extending outward from a peripheral edge of the second active material layer.

3. The battery according to claim 1, wherein The area of ​​the first active material layer side extension and the second active material layer side extension in plan view, whichever is larger, is defined as C. When the area of ​​the solid electrolyte sheet in a plan view is defined as A, The ratio of area C to area A is 1 / 20 or less.

4. The battery according to claim 1, wherein The solid electrolyte sheet has a thickness of 3 μm or more and 100 μm or less.

5. The battery according to claim 1, wherein The solid electrolyte sheet has a ratio of the solid electrolyte of 50.0 mass % or more and 99.5 mass % or less.

6. The battery according to claim 1, wherein The solid electrolyte sheet has a support.

7. The battery according to claim 6, wherein The support body is formed of a porous substrate, and the solid electrolyte is supported in pores of the porous substrate.

8. The battery according to claim 1, wherein The solid electrolyte includes a crystal phase having an argyrodite-type crystal structure.

9. The battery according to claim 1, wherein The first active material is a positive electrode active material, and the second active material is a negative electrode active material.

10. The battery according to claim 9, wherein The two stacked structures are connected in series so that the first active material layer in one of the stacked structures faces the second active material layer in the other stacked structure via the current collector.

11. The battery according to claim 1, wherein The first active material and the second active material are both positive electrode active materials or negative electrode active materials.

12. A self-supporting battery stack structure comprising: a solid electrolyte sheet comprising a solid electrolyte; a first active material layer formed on one main surface of the solid electrolyte sheet and containing a first active material; and The second active material layer is formed on the other main surface of the solid electrolyte sheet and contains a second active material.

13. The battery stack structure according to claim 12, wherein: The battery stack structure has a punching-out portion that penetrates the solid electrolyte sheet, the first active material layer, and the second active material layer in a thickness direction.

Citation Information

Patent Citations

  • Bipolar battery, battery pack and vehicle with them mounted thereon

    JP2007213930A

  • Sheet with metal eyelet, and fringe tape used for the same

    JP2007259734A

  • Solid electrolyte sheet and all-solid-state lithium ion battery

    JP2018129307A